2008
DOI: 10.1038/nsmb.1413
|View full text |Cite
|
Sign up to set email alerts
|

The Ino80 chromatin-remodeling enzyme regulates replisome function and stability

Abstract: Previous studies have demonstrated essential roles for ATP-dependent chromatin-remodeling and chromatin-modifying enzymes in gene transcription and DNA repair, but few studies have addressed how the replication machinery deals with chromatin. Here we show that the Ino80 remodeling enzyme is recruited to replication origins as cells enter S phase. Inducible degradation of Ino80 shows that it is required continuously for efficient progression of forks, especially when cells are confronted with low levels of repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 44 publications
6
150
1
Order By: Relevance
“…INO80-deficient mammalian cells show sensitivity to hydroxyurea, and are defective in both S-phase progression and recovery from replication stress (Hur et al, 2010;Min et al, 2013;Vassileva et al, 2014). Enrichment of INO80 at stalled replication forks has been detected in yeast by ChIP analysis (Papamichos-Chronakis and Peterson, 2008;Shimada et al, 2008). Furthermore, yeast lacking in functions of both INO80 and ISW2 cannot recover from the S-phase checkpoint (Au et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…INO80-deficient mammalian cells show sensitivity to hydroxyurea, and are defective in both S-phase progression and recovery from replication stress (Hur et al, 2010;Min et al, 2013;Vassileva et al, 2014). Enrichment of INO80 at stalled replication forks has been detected in yeast by ChIP analysis (Papamichos-Chronakis and Peterson, 2008;Shimada et al, 2008). Furthermore, yeast lacking in functions of both INO80 and ISW2 cannot recover from the S-phase checkpoint (Au et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other evidence showed that ISWI type nucleosome remodeling complex SNF2h is recruited to replication fork by WTSF, RNAi mediated knock down of SNF2h or WTSF caused reduction of DNA replication efficiency during S phase (Poot et al, 2004). In S. cerevisia INO80 complex is enriched in replication origins and stalled replication forks under replicative stress (Papamichos-Chronakis and Peterson, 2008;Vincent et al, 2008). Furthermore, mutation of INO80 leads to loss of replisome proteins under replicative stress (Papamichos-Chronakis and Peterson, 2008).…”
Section: Disassembly Of Chromatin Structure Ahead Of Replication Forkmentioning
confidence: 99%
“…In S. cerevisia INO80 complex is enriched in replication origins and stalled replication forks under replicative stress (Papamichos-Chronakis and Peterson, 2008;Vincent et al, 2008). Furthermore, mutation of INO80 leads to loss of replisome proteins under replicative stress (Papamichos-Chronakis and Peterson, 2008).…”
Section: Disassembly Of Chromatin Structure Ahead Of Replication Forkmentioning
confidence: 99%
“…2,3 To plough through chromatin the replication machinery needs to mobilize and evict nucleosomes and there is evidence that nucleosome remodeling helps to clear the path for efficient progression of the replication fork. [4][5][6] Remodeling may also be involved in the initiation of replication and origin definition, although less is known about this aspect. 2,7 Behind the replication fork, nucleosome remodeling contributes to the reformation of higher order chromatin structures.…”
Section: Keeping Chromatin Quietmentioning
confidence: 99%
“…[24][25][26][27][28][29] Depletion of SMARCAD1 in human cancer cell lines leads to the global accumulation of acetylated histones H3 and H4, a stalled replication forks. 5,[11][12][13] The ACF complex, consisting of the ATPase SNF2h and Acf1, appears to facilitate the progression of replication through highly condensed mammalian chromatin; its depletion causes a delay in S-phase progression that is reversible upon chromatin decondensation. 4 This suggests a function for ACF in establishing an accessible chromatin structure ahead of the replication machinery.…”
Section: Maintaining Silence Through Remodeling: a New Playermentioning
confidence: 99%